2021
DOI: 10.1089/scd.2021.0065
|View full text |Cite
|
Sign up to set email alerts
|

Wharton's Jelly Mesenchymal Stem Cell-Derived Extracellular Vesicles Reduce SARS-CoV2-Induced Inflammatory Cytokines Under High Glucose and Uremic Toxin Conditions

Abstract: Cytokine storm is recognized as one of the factors contributing to organ failures and mortality in patients with COVID-19. Due to chronic inflammation, COVID-19 patients with diabetes mellitus (DM) or renal disease (RD) have more severe symptoms and higher mortality. However, the factors that contribute to severe outcomes of COVID-19 patients with DM and RD have received little attention. In an effort to investigate potential treatments for COVID-19, recent research has focused on the immunomodulation function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 54 publications
1
20
0
Order By: Relevance
“…We showed that HG levels enhanced ACE2 mRNA and protein expression levels in Calu-3 cells via GLUT1 in a dose-and time-dependent manner. Vuong Cat Khanh et al already showed ACE2 expression in Calu-3 cells were enhanced under high glucose concentration [16]., and we found that GLUT1 is the receptor to enhance expression of ACE2. SARS-CoV-2 enters host cells using viral surface transmembrane spike (S) glycoprotein [17].…”
Section: Discussionsupporting
confidence: 62%
“…We showed that HG levels enhanced ACE2 mRNA and protein expression levels in Calu-3 cells via GLUT1 in a dose-and time-dependent manner. Vuong Cat Khanh et al already showed ACE2 expression in Calu-3 cells were enhanced under high glucose concentration [16]., and we found that GLUT1 is the receptor to enhance expression of ACE2. SARS-CoV-2 enters host cells using viral surface transmembrane spike (S) glycoprotein [17].…”
Section: Discussionsupporting
confidence: 62%
“…In addition to n6-acetyl-l-lysine, data showed significantly upregulated levels of the protein-bound uremic retention solute p-cresol ( p < 0.05) in COVID-19 overweight-obese patients when compared to COVID-19 lean patients ( Figure 3B ). P-cresol is known to associate with increased admissions of hospitalizations due to infections ( 36 ). Moreover, its high levels is usually correlated with chronic inflammation and cardiovascular diseases ( 37 ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, findings from in vitro work with human lung adenocarcinoma epithelial cells (Calu-3 cells) also indicates that uremic toxin p-cresol contributes to the induction of cytokine storm in response to SARS-CoV. Culturing Calu-3 cells with p-cresol induced responses that exhibited enhanced expression and secretion of the proinflammatory tumor necrosis factor (TNF-α), Interleukins (IL-6 and IL-1β), and interferon gamma (IFNγ) cytokines ( 36 ). This suggests that our identified metabolic signatures, N6-acetyl L-Lysine and p-Cresol, are potentially involved in inducing cytokine storm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both studies were completed without any adverse events or safety concerns. Recently, Khanh et al reported that the Wharton's jelly MSC-derived EVs showed significant reduction in nuclear NF-κB p65 and suppression of the cytokine storm in COVID-19 patients suffering from diabetes mellitus or renal disease [ 104 ].…”
Section: Stem Cell-derived Extracellular Vesicles In Covid-19 and Acu...mentioning
confidence: 99%